Refractory hyperactivity and Batten's disease – A Case Report - Narayan R Mutalik; Vinayak Koparde; Devaraddi Navalli (Archives of Mental Health, 2016)
Attention deficit hyperactivity disorder (ADHD) is a psychiatric disorder of neurodevelopmental type characterized by inattentiveness, hyperactivity and impulsiveness. Batten disease is said to be the commonest form among neuronal ceroidlipofuscinoses (NCL). Though it is rare, it begins in childhood as fatal neurodegenerative disorder. We are presenting a rare case suffering from a combination of these two disorders and the management was a challenging task